Business Development Strategy to Improve Profit Margins in Gas Stations Facing Industry Disruptions - Patrick Ekklesio Harazaki Dachi; Manahan Parlindungan Saragih Siallagan (Green Publisher Indonesia, 2026)
The Indonesian gas station industry faces structural challenges from rising operational costs, regulatory pressures, intensified competition, and mobility electrification. Gas stations in Jakarta experience shrinking profit margins as operational expenses increase while fuel margins remain strictly regulated. This study aims to analyze the key operational cost drivers contributing to shrinking profit margins and to explore strategic approaches that gas station owners can adopt to improve profitability. This research adopts a mixed-methods approach, combining qualitative interviews with gas station managers and supervisors, quantitative customer surveys, and strategic analysis frameworks including PESTEL, Porter's Five Forces, Resource-Based View (RBV), VRIO analysis, and SWOT-TOWS formulation. The findings indicate that declining profit margins are mainly driven by rising utility costs, particularly electricity consumption for lighting, compressors, and fuel dispensers, increasing labor expenses such as wages and overtime, and higher maintenance costs due to aging infrastructure and the absence of preventive maintenance systems. Operational inefficiencies—including inconsistent service quality, equipment downtime, and long customer queues—also reduce revenue potential. Additionally, the limited development of non-fuel revenue streams increases dependence on regulated fuel margins. This study proposes a strategic improvement framework integrating operational excellence and business model innovation. Recommended strategies include improving facility conditions and service standards, implementing preventive maintenance and staff training programs, optimizing queue management, expanding non-fuel retail services, and adopting digital technologies. The framework also highlights the importance of preparing EV charging infrastructure to align with Indonesia’s national energy transition policies